Relação universidade-empresa no Rio Grande do Sul em busca de inovação para o estado - Sala, Gabriela Dalla Vecchia (2020)
The present study is intended to understand the relationship between university and business sector, forwarding innovation to Brazil, through scientific-technological projects. The research consists through the disparities observations, such as the Global Innovation Index, which classifies the country in the 66th position in 2019 in relation to the innovation aspect (CORNELL; INSEAD; WIPO, 2019), while the U.S. National Science Foundation (NSF) classifies the research and development (R&D) in Brazil's university in the 12th position in 2016 in terms of engineering and science articles (NSF, 2018). The aim of the study was to identify and understand the motivations involved with regard to university-business sector. From the theoretical evidences, an exploratory research was conducted with some representatives of Rio Grande do Sul universities and companies. Due to the qualitative approach, primary data was collected through in-depth interviews with thirty one interviewed. Of total, eighteen were university leaders and researchers and thirteen were R&D leaders or business leaders from the business sector. In the inexistence of relations the presence of prejudice was identified, originating from the lack of knowledge of another's reality. When the existence of the relation between university and business sector was identified, difficulties were observed which impact their association and result in the low interactions performance, influencing the development, expansion and the continuity of the scientific-technological projects and in the potential reach of innovation. With the testimonies collected, interests fulfilled and unfulfilled for both players have been recognized, existing or not the implementation of the university-business sector relationship. The situations referred indicate a communication failure in the beginning or in the middle of the project, in the relationships developed inappropriately or in the distance between the players of the university and business sector.